Nanofluidics and microfluidics : systems and applications - Prakash, Shaurya; Yeom, Junghoon (Waltham : William Andrew, 2014)
To provide an interdisciplinary readership with the necessary toolkit to work with micro- and nanofluidics, this book provides basic theory, fundamentals of microfabrication, advanced fabrication methods, device characterization methods and detailed examples of applications of nanofluidics devices and systems. Case studies describing fabrication of complex micro- and nanoscale systems help the reader gain a practical understanding of developing and fabricating such systems. The resulting work covers the fundamentals, processes and applied challenges of functional engineered nanofluidic systems.--
Includes bibliographical references and index.
Keywords: Microfluidics -- Handbooks, manuals, etc; Nanofluids -- Handbooks, manuals, etc; Systems biology -- Handbooks, manuals, etc; Biotechnology -- Handbooks, manuals, etc; Cell physiology -- Handbooks, manuals, etc